Relationship between NRT measurements and behavioral levels in children with the Nucleus 24 cochlear implant may change over time: preliminary report - Thai-Van, Hung; Chanal, Jean-Marc; Coudert, Chrystelle; Veuillet, Evelyne; Truy, Eric; Collet, Lionel (International journal of pediatric otorhinolaryngology, 2001)
Objective: Response from spiral ganglion cells to electrical stimulation via the Nucleus 24 cochlear implant can be measured using the neural response telemetry system. The purpose of this study was to assess, in children, the correlation between the neural response threshold and the behavioral levels used for cochlear implant programming process. Methods: The neural response telemetry test was administered to 23 children (mean age at implantation: 4 years) with the Nucleus 24 cochlear implant. Four intra-cochlear electrodes (electrodes 5, 10, 15 and 20) were tested. The neural response threshold at 3, 6, 9 and 12 months post-implantation was compared with the behavioral threshold and the maximum comfort level estimated during the same periods: a Pearson's correlation test was performed for each tested electrode. Results: On apical electrodes, the correlation with the behavioral threshold remained significant from 3 to 12 months post-implantation ( r ranging from 0.696 to 0.909, P<0.05), and the correlation with the maximum comfort level was also significant throughout the study period, except on electrode 15 at 9 months (tendency to significance). On basal and intermediate electrodes, statistical correlations were found only at some points of time; nonetheless, at 12 months post-implantation, a significant correlation with behavioral levels could be clearly demonstrated both on electrode 15 ( r=0.914–0.778, P<0.05) and on electrode 10 ( r=0.845–0.720, P<0.05). Conclusions: This preliminary study suggests that the correlation between the neural response threshold and behavioral levels may improve from the base towards the apex of the cochlea. However, a significant correlation can be demonstrated for all tested electrodes at 12 months post-implantation. During the first months post-implantation care must be exercised when interpreting neural response telemetry measurements: a positive test does not necessarily mean that the stimulus delivered to the acoustic nerve will be centrally processed with the result of an auditory perception.